Implementasi Pendidikan Karakter Berbasis Islami di Mts Raudhatul Akmal - Syarifah Widya Ulfa; Herika Iranti Sanjaya; Devi Indah Sari; Hodi Alfian; Ibnati Mawaddah (Peneliti.net, 2022)
The goals and ideals of the Indonesian nation are to realize the lives of citizens who have the nation's intellectuals listed in the 1945 Constitution, the government and citizens jointly solve educational problems so that a nation that is strong, independent and ready to face the world of globalization is formed. The world of education is currently experiencing the problem of fading the character of students, this can be observed especially in today's young generation. This article aims to find out the form of implementing Islamic-based character education at MTs Raudhatul Akmal and find out what factors cause obstacles in efforts to implement forms of Islamic-based character education at MTs Raudhatul Akmal. This research uses descriptive qualitative method. The data collection technique used was observation, interviews and documentation by observing directly in the field. Based on the results of data analysis, it can be found that the form of implementing Islamic-based character education is in camping and MABIT (Faith Development Night and TaQwa) and extracurricular activities and through positive habituation activities to read the Koran and pray dhuha in congregation as well as exemplary behavior. The inhibiting factors/obstacles for schools in implementing character education at MTs Raudhatul Akmal are facilities and infrastructure, students and teacher potential.